Functionalization of multi-walled carbon nanotubes by radiation-induced graft polymerization in aqueous solution. Issue 4 (3rd April 2017) - Zhang, Dong-Li; Zha, Jun-Wei; Li, Chao-Qun; Li, Wei-Kang; Li, Jian-Xi
ABSTRACT: A facile strategy for the preparation of water-soluble multi-walled carbon nanotubes (MWCNTs) in aqueous solution is proposed, where MWCNTs were treated by the concentrated mix acid and then functionalized by simultaneous radiation-induced graft polymerization of acrylic acid under the γ-ray. The structure of the grafted MWCNTs (denoted as MWCNT-g-PAAc) is characterized by means of FT-IR, l H NMR, Raman spectroscopies, TGA analysis, and TEM imaging. The degree of grafting was dependent on the reaction conditions such as the monomer concentration and the inhibitor concentration. The stability of the aqueous solution of MWCNT-g-PAAc is highly improved, where the solution is stable for more than 30 days at the concentration 1.5 g/L.